Magnetic resonance imaging brain findings of pediatric HIV cases and its correlation with clinical and immunological stages of the disease: A study from a tertiary care center of Rajasthan - Sulaniya, Pawan K; Sulaniya, Chandrakanta; Singh, Jagdish; Garg, Kapil (Indian Journal of Child Health, 2017)
Objective: To study the magnetic resonance imaging (MRI) brain findings in pediatric HIV patients and to correlate them with clinical and immunological staging. Methods: This study was conducted in the Department of Pediatrics of a Teaching Institute of Rajasthan. It was a prospective longitudinal study, conducted over a period of 15 months (April 2008-July 2009). Diagnosis of HIV was confirmed and classified in clinical stages and immunologic stages as per NACO guidelines. MRI brain was done in every patient. Patients with abnormal MRI brain findings were further studied and correlated with clinical findings and CD4+ cell counts. Results: We had total 109 HIV-positive patients registered with us; out of these, 90 were in regular follow-up. Out of these 90 patients, 16 subjects (17.78%) showed abnormal neuroimaging features on MRI brain. No case presented with abnormal MRI features in clinical Stage I and II. 4 were in clinical Stage III, and 12 were in Stage IV. No case presented with abnormal MRI in immunological Stage I and II. 5 cases (31.25%) were in immunological Stage III and 11 (68.75%) in Stage IV. Out of total 90 subjects, only 10 patients had abnormal clinical (neurological) manifestations and rested 80 patients were neurologically and developmentally normal. 6 out of 16 (37.5%) patients with abnormal MRI brain findings did not show any neurological manifestations. The most common MRI brain abnormality noted was cerebral atrophy in 7 (43.75%) cases followed by nonspecific demyelination in 31.25% cases, and ventriculomegaly, nonspecific calcification, and infarcts in 3 (18.75%) subjects each and cerebellar atrophy in 2 subjects. Conclusions: Our study demonstrated that abnormalities of MRI brain increases with increasing immunosuppression and advancing clinical stage. We did not found any significant correlation with age and sex with abnormal MRI brain findings. Importantly, HIV?positive children may present with only abnormal MRI brain findings without any clinical manifestation.